Engineering Pseudomonas protegens Pf‐5 to improve its antifungal activity and nitrogen fixation - Jing, Xiaoshu (Microb Biotechnol, 2018)
In agricultural production, sustainability is currently one of the most significant concerns. The genetic modification of plant growth‐promoting rhizobacteria may provide a novel way to use natural bacteria as microbial inoculants. In this study, the root‐colonizing strain Pseudomonas protegens Pf‐5 was genetically modified to act as a biocontrol agent and biofertilizer with biological nitrogen fixation activity. Genetic inactivation of retS enhanced the production of 2,4‐diacetylphloroglucinol, which contributed for the enhanced antifungal activity. Then, the entire nitrogenase island with native promoter from Pseudomonas stutzeri DSM4166 was introduced into a retS mutant strain for expression. Root colonization patterns assessed via confocal laser scanning microscopy confirmed that GFP‐tagged bacterial were mainly located on root surfaces and at the junctions between epidermal root cells. Moreover, under pathogen and N‐limited double treatment conditions, the fresh weights of seedlings inoculated with the recombinant retS mutant‐nif strain were increased compared with those of the control. In conclusion, this study has innovatively developed an eco‐friendly alternative to the agrochemicals that will benefit global plant production significantly.